The Establishment And Activity Of Military Judicial Commissions In The Turkestan General Governorate - B.G. Rasulov (Genius Journals, 2025)
This article presents information on the organization, structure, and activities of the Military Judicial Commissions operating in the Turkestan Krai, based on the audit report of the Emperor’s secret advisor, Fedor Karlovich Girs.
Keywords: Turkestan; F.K. Girs; Military Judicial Commissions